PERBEDAAN PENGGUNAAN MEDIA GAMBAR DAN MEDIA AUDIOVISUAL DALAM KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELAS XI SMA EKASAKTI PADANG - Marisya, Susanti (STKIP Pesisir Selatan, 2022)
This research is motivated by the low ability to write procedure texts and Lack of student interest in writing procedure text. The purpose of this study is first, to describe the use of image media in the ability to write procedural texts for class XI students of SMA Ekasakti. Second, to describe the use of audiovisual media in writing procedural texts for class XI students of SMA Ekasakti. Third, describe the differences in the use of image media and audiovisual media in the ability to write procedural texts for class XI students of SMA Ekasakti Padang. This type of research is quantitative with a comparative method. The research data are in the form of test results for writing procedural texts. The population in the study were all students of class XI totaling 38 students. Sampling was carried out with a total sampling of 38 students consisting of two class XI IPA 20 students and class XI IPS 18 students. The research instrument was in the form of a procedural text writing ability test. The results showed that first, the use of image media in writing procedure text in class XI IPS SMA Ekasakti was in the medium category (40.7%) with an average value of 66.00. Second, the use of audiovisual media in class XI IPA SMA Ekasakti is in the high category (54.4%) with an average score of 79.00. Third, there is a difference between students writing procedure texts for class XI SMA Ekasakti students using audio-visual media (79.00) and picture media (66.00).